NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL BUMI KARYA TERE LIYE DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Fitri Pricilia Putri; Afnita Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of this study is to explain the value of character education in the novel Bumi by Tere Liye and how its implication in learning. This research is a qualitative study using descriptive methods. The data source is the novel Bumi by Tere Liye. The value of character education contained in the novel, including: (1) honesty, (2) discipline, (3) curiosity, (4) national spirit, (5) friendly and communicative, (6) fond of reading, (7) social care, and (8) responsibility. In total there are 18 data, the highest value is the value of curiosity character education. Kata Kunci: nilai pendidikan karakter, novel, Tere Liye